Analisis Supervisi Akademik pada Peningkatan Kinerja Guru - Rida Rimadani; Teguh Triwiyanto (Aqlamuna: Journal of Educational Studies, 2023)
The analysis of academic supervision was conducted to find out how the process of implementing academic supervision ideally has an impact on improving teacher performance. The research was conducted using a literature review approach that collected data and information from several scientific journal studies that have various characteristics. From the data collection, two big data were drawn which were discussed in general and also comparatively to analyze the academic supervision process comprehensively starting from the planning, implementation, and assessment system of academic supervision. In the findings of this research, it is found that each school has its own uniqueness and method in implementing academic supervision which is expected to help solve problems that have not been resolved so that ideal and quality improvements can be made. Improving teacher performance is expected to improved the quality of learning.